Electrical Energy Audit at Faculty of Technology Management and Business, Universiti Tun Hussein Onn Malaysia - Ahmad Kamal, Muhammad Aliff Nadzmi; Mohd Yusuf, Mohd Fairouz (Evolution in Electrical and Electronic Engineering, 2023)
Energy consumption may increase due to some factors such as surrounding temperature and humidity. The inefficient system operated will demand more energy to provide a comfortable and healthy environment. Besides, it is very important to have an energy audit because to Efficient Management of Electrical Energy Regulations 2018 (EMEER) is the regulation that was enacted to improve energy management practices among large energy consumers. This paper presents the energy audit at the Faculty of Technology Management and Business (FPTP), UTHM. The audit process includes the findings of the building (illuminance, temperature, humidity, and thermal energy) through a walkthrough and detailed measurements. Excessive usage of electricity may be caused by the low energy management in the building. Inefficient systems may lead to energy waste and other issues. The specification of the system, such as lighting, and chillers, must follow the standardization (MS1525:2014) to provide a good visual environment and comfortable air. All data and information had been analyzed that showed some inefficient system operation. Energy Saving Measure (ESM) obtained and proposed to reduce energy consumption and cost. The implementation of Energy saving in a building will make the building’s system more efficient which reduces energy consumption, and cost-saving.